Chest-to-Back Skin-to-Skin Contact to Regulate Body Temperature for Low Birth Weight and/or Premature Babies: A Crossover Randomized Controlled Clinical Trial - Sisay Gere; Yemane Berhane; Alemayehu Worku (International Journal of Pediatrics)
Skin-to-skin contact (SSC) is one of the critical components of kangaroo mother care (KMC), which is an intervention to enhance the survival of low birth weight (LBW) and/or premature infants in low-income settings. Chest-to-chest (CC) contact has been practiced widely; however, mothers face practical challenges to continuously provide CC-SSC. Hence, we assessed the efficacy of chest-to-back (CB) SSC as an alternative to CC-SSC in regulating body temperature for LBW and/or premature babies in Ethiopia. We applied a noninferiority clinical trial among LBW and/or premature infants admitted to a referral hospital neonatal intensive care unit (NICU) in Ethiopia. The study randomized the infants into two crossover arms; arm 1 applied first CB-SSC followed by CC-SSC, and arm 2 applied first CC-SSC followed by CB-SSC. The outcome measure was a change in skin temperature. We used a linear mixed-effect model for analysis. The result showed no statistically significant difference in the mean temperature between the comparison arms. In conclusion, we found that the CB-SSC was not inferior to the CC-SSC in regulating body temperature of the babies. Thus, CB-SSC can be further investigated as an alternative to CC-SSC in the kangaroo care model in low-income settings.